Improved oxidation resistance of Mg-9Al-1Zn alloy microalloyed with 60 wt ppm Be attributed to the formation of a more protective (Mg, Be)O surface oxide. (March 2018) - Tan, Qiyang; Mo, Ning; Lin, Chih-Ling; Jiang, Bin; Pan, Fusheng; Huang, Han; Atrens, Andrej; Zhang, Ming-Xing
Graphical abstract: Highlights: The oxidation resistance of Mg-9Al-1Zn was improved by microalloying with 60 wt ppm Be. Be reinforced the initially formed MgO layer by Be accumulation to form fine-grained (Mg, Be)O solid solution. The fine-grained (Mg, Be)O layer exhibited mechanical strength higher than that of MgO layer. During high temperature oxidation, the fine-grained (Mg, Be)O layer provided sufficient strength against layer cracking. Abstract: The oxidation resistance of Mg-9Al-1Zn alloy (AZ91) was significantly improved through microalloying with 60 ppm Be. Be reinforced the initially formed oxide layer on the alloy surface by (i) the formation of a (Mg, Be)O solid solution due to the Be enrichment; and (ii) the refined gains of the (Mg, Be)O. During high-temperature oxidation, the reinforced (Mg, Be)O layer provided sufficient strength to withstand the internal stresses and the Mg vaporisation, and therefore delayed the oxide layer cracking and debonding from the substrate. In addition, the initial oxidation rates of AZ91 and Be-containing AZ91 were closely related to surface roughness.